Characteristics of Using Action Games in Secondary Schools (Eurasian Journal of Learning and Academic Teaching, 2023)
In this article, the use of mobile games as a means of physical education in the education of physical qualities in school-age children through the use of mobile games and on this basis, to determine the theoretical foundations and methodological ways of developing the technology of children's motor activity in the conditions of general education schools and to achieve the goal It is planned to conduct research by organizing physical education and public health activities for the development of children's movement activity in the course of general education.